English is an Asian Language: Do Our Textbooks Reflect This? - Toh Knon Peng (TEFLIN Journal: A publication on the teaching and learning of English, 1997)
Abstract: Because of the economic boom, the extensive use of English, and the vital process of acculturation, English is now used in South East Asia to communicate amongst South East Asians, to express sociocultural meanings. Hence English should not be treated as a foreign language and learners of English should be firmly grounded in their own culture, traditions and values.